Does the Preoperative Neutrophil-to-lymphocyte Ratio and Platelet-to-lymphocyte Ratio Associate with Clinic-pathological Characteristics in Papillary Carcinoma of Thyroid - Shrestha, B. L.; KC, A. K.; Rajbhandari, P.; Dhakal, A.; Shrestha, K. S. (Kathmandu University Medical Journal, 2021)
Background Thyroid cancer is associated with local and systemic inflammatory activities. Many systemic inflammatory markers including the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) had shown credible and independent prognostic biomarkers in different malignant conditions. These markers are easy to reproduce, measure and inexpensive also. So, the preoperative evaluation of NLR and PLR is helpful in evaluating tumor growth and prognosis of papillary carcinoma of thyroid. Objective To evaluate the association of pre-operative NLR and PLR with clinic-pathological characteristic in papillary carcinoma of thyroid. Method This was a retrospective study performed in thirty one patients with the diagnosis of papillary carcinoma of thyroid. Preoperative NLR and PLR values were correlated with the clinical parameters like age, gender, lymph node metastasis, tumor size and pathological features (e.g., multifocality, bilaterality, extrathyroidal spread). Result There were thirty one patients, amongst which 13 were male and 18 were female. Similarly, the age distribution ranges from 27-68 years. The value of NLR was 2.37±1.09, and the value of PLR was 96.69±49.53.The increase in NLR was associated with increase in tumor size with statistically significant results. Similarly, increase in PLR was associated with increase in tumor size and multifocality with statistically significant results. Conclusion Increase NLR and PLR is associated with lymph node metastasis, extra thyroidal extension, multifocality of tumor and also bilaterality, so the risk can be stratified beforehand with measurement of NLR and PLR.